2011
DOI: 10.1002/jcb.23160
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of systemic lupus erythematosus by withangulatin A in MRL/lpr mice

Abstract: We have previously reported the anti-inflammatory potential and the possible underlying mechanisms of Withangulatin A (WA), which is an active component isolated from Physalis angulata L. Here, we demonstrated that WA might improve the life quality, as well as reduced the accumulation of proteinuria symptoms and levels of anti-double-stranded DNA antibodies in MRL/lpr mice. Moreover, WA could improve renal histopathologic characteristics of MRL/lpr mice. Intriguingly, expression of B cell-activating factor (BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…44,45 Spleen weights were, however, not affected in MRL/lpr Fn14-KO mice. Moreover, there were no significant differences in splenic immune cell subpopulations, indicating little to no influence of Fn14 deficiency on the systemic immune response.…”
Section: Discussionmentioning
confidence: 88%
“…44,45 Spleen weights were, however, not affected in MRL/lpr Fn14-KO mice. Moreover, there were no significant differences in splenic immune cell subpopulations, indicating little to no influence of Fn14 deficiency on the systemic immune response.…”
Section: Discussionmentioning
confidence: 88%
“…87 It was somewhat perplexing that proteinuria and glomerulonephritis were not as markedly increased in MRL/lpr mice at 18 weeks-of-age as many others have reported for the strain. 88,89 Possibly having the treatment regime progress for a longer period of time would have allowed us to determine more significant differences between the treated and the untreated groups. However, the downside of a prolonged treatment could either overshoot the window of therapeutic effects of 17-DMAG or risk the loss of untreated animals due to disease as several reports have shown 50% mortality for MRL/lpr mice after 20 weeks of age, with disease expression by the 14-16 week.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 99%
“…However, the downside of a prolonged treatment could either overshoot the window of therapeutic effects of 17-DMAG or risk the loss of untreated animals due to disease as several reports have shown 50% mortality for MRL/lpr mice after 20 weeks of age, with disease expression by the 14-16 week. 32,89,90 Another pathological aspect of MRL/lpr mice is the presence of splenomegaly in mice exhibiting disease. 59 We found that splenomegaly was reduced in mice treated with the HSP90 inhibitor 17-DMAG.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 99%
“…The medical treatment for SLE patients are non-steroidal anti-inflammatory drug (NSAID), anti-malaria (chloroquine), steroid, immunosuppressant or cytotoxic (azathioprine, cyclophosphamide, mycophenolate mofetil, methotrexate, cyclosporine A), and another therapy such as monoclonal antibody (rituximab, belimu-mab). [3][4][5][6] Generally, methylprednisolone becomes the main therapy for SLE patients who have high, moderate, and low intensity of activities, or as a maintenance dose. 3 Therapy supplement by consuming herbs can be an alternative for SLE treatment.…”
Section: Introductionmentioning
confidence: 99%
“…which has a high immunosuppresant activity, therefore, it can be used to control autoimmune disease. 5,6 WA might reduce the accumulation of proteinuria symptoms and levels of anti-doublestranded DNA antibodies in animal model. Moreover in animal model, WA could improve renal histopathologic characteristics and reduced an expression of B cell-activating factor (BAFF), BAFF-R and related gene in the spleen.…”
Section: Introductionmentioning
confidence: 99%